Hubungan Self-Efficacy dan Self-Regulated Learning dengan Goal Orientation pada Siswa SMA - Selviana (Fakultas Psikologi Universitas Pancasila, 2016)
The aim of this study was to investigate if there was a correlation between self-efficacy and self-regulated learning with goal orientation among senior high school students in Jakarta. This study hypothesized there was a positive correlation between self-efficacy and self-regulated learning with goal orientation among senior high school students in Jakarta. The participants of this study were senior high school students at SMAN 40 Jakarta, grade XI. The sampling technique used in this study was cluster random sampling. This study used a quantitative approach and used goal orientation scale, self-efficacy scale, and self-regulated learning scale to collect the data and was analyzed with discriminant analysis and cross tabs eta. The result of this research is fit with the hypothesis.